Prevalence of stress, anxiety, depression, and reported self-esteem among mothers of children with autism spectrum disorder - Poyyaamozhi, Punitha; Joseph, Leonard; Nambi, Shanthi; K, Raman; Inbadurai , Palaniswami; V, Rewanth Kumar; Muya, Christine (Journal of Associated Medical Sciences, 2025)
Background: Mothers of children with autism spectrum disorder (ASD) have an increased risk of depression, anxiety, stress, and diminished self-esteem due to the numerous challenges involved in raising children with socio-behavioural difficulties. Objectives: This study investigated the prevalence of depression, anxiety, stress, and low self-esteem among mothers of children with ASD. Materials and methods: A cross-sectional descriptive study was conducted among 246 mothers of children with ASD. The prevalence of depression, anxiety, and stress was assessed using the Depression, Anxiety and Stress Scale-21 Items, and self-esteem was measured using Rosenberg’s Self-Esteem Scale. Demographic data for both mothers and children were collected using a pro forma. Data are summarised as frequencies, means (M), standard deviations (SD), and percentages. Results: The prevalence rates among mothers were as follows: depression, 84.14% (N=207); anxiety, 77.2% (N=190); stress, 74% (N=167); and diminished self-esteem, 67.9% (N=167). Mean severity scores indicated moderate levels of depression (M=17.26, SD=7.7), anxiety (M=12.7, SD=7.7), and stress (M=19.49, SD=8.0), and low self-esteem (M=23.25, SD=9.5). Conclusion: Mothers of children with ASD had high prevalence rates of depression, anxiety, stress, and low self-esteem. These findings highlight the psychological challenges faced by mothers caring for children with ASD. Therapeutic interventions should therefore address the mental health needs of these mothers alongside the rehabilitation of their children.